Lung Ultrasound in the Diagnosis of COVID-19 Pneumonia: Not Always and Not Only What Is COVID-19 “Glitters” - Quarato, Carla Maria Irene; Mirijello, Antonio; Maggi, Michele Maria; Borelli, Cristina; Russo, Raffaele; Lacedonia, Donato; Foschino Barbaro, Maria Pia; Scioscia, Giulia; Tondo, Pasquale; Rea, Gaetano; Simeone, Annalisa; Feragalli, Beatrice; et al. (Frontiers in Medicine, 2021)
Background. In the current COVID-19 pandemic, lung ultrasound (LUS) has been extensively employed to evaluate lung involvement and proposed as a useful screening tool for early diagnosis in Emergency Department (ED), pre-hospitalization triage and treatment monitoring of COVID-19 pneumonia. However, the actual effectiveness of LUS in characterizing lung involvement in COVID-19 is still unclear. Our aim was to evaluate LUS diagnostic performance in assessing or ruling out COVID-19 pneumonia when compared with chest CT (gold standard) in a population of SARS-CoV-2 infected patients. Methods. A total of 260 consecutive RT-PCR confirmed SARS-CoV-2 infected patients were included in the study. All the patients underwent both chest CT scan and concurrent LUS at admission, within the first 6–12 h of hospital stay. Results. Chest CT scan was considered positive when showed a “typical” or “indeterminate” pattern for COVID-19, according to the RSNA classification system. Disease prevalence for COVID-19 pneumonia was 90.77%. LUS demonstrated a sensitivity of 56.78% in detecting lung alteration. The concordance rate for the assessment of abnormalities by both methods increased in case of peripheral distribution and middle-lower lung location of lesions and in cases of more severe lung involvement. A total of 9 patients had a “false positive” LUS examination. Alternative diagnosis included chronic heart disease (6 case), bronchiectasis (2 cases) and subpleural emphysema (1 case). LUS specificity was 62.50%. Collateral findings indicative of overlapping conditions at Chest CT were recorded also in patients with COVID-19 pneumonia and appeared distributed with increasing frequency passing from the group with mild disease (17 cases) to that with severe disease (40 cases). Conclusions. LUS does not seem an adequate tool for screening purposes in the ED, due to the risk of missing some lesions and/or to underestimate the actual disease's extent. Furthermore, the not specificity of LUS implies the possibility to erroneously classify pre-existing or overlapping conditions as COVID-19 pneumonia. It seems more safe to integrate a positive LUS examination with clinical, epidemiological, laboratory and radiologic findings to suggest a “virosis”. Viral testing confirmation is always required.